University-timetabling problem and its solution using GELS algorithm: a case study. (2018) - Nategh, Majid Nikougoftar; Hosseinabadi, Ali Asghar Rahmani; Balas, Valentina Emilia
Course scheduling includes a large volume of data with numerous constraints and unchangeable specifications and each university deals with several times a year. Course scheduling is a NP-hard problem and using traditional methods to solve it is very difficult. But evolutionary algorithms suggest good solutions for this type of problems. In this paper we used gravitational emulation local search algorithm to solve the course scheduling problem which is an evolutionary algorithm. Results demonstrate the good quality of time table provided by the proposed algorithm and also decreased time against other algorithms.